Analisis Framing model Entman pada Berita Republika tentang Gua Safarwadi: Antara Mitos Dan Rasionalitas - Eko Agoes Setiawan (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
This study examines media framing of Muslim public belief in Safarwadi Cave, which is claimed to be able to “connect to Mecca,” as reported by Republika. Employing a qualitative approach and Robert Entman’s framing analysis model, the study explores how the media define the problem, diagnose its causes, make moral judgments, and propose remedies regarding this religious phenomenon. The primary data consist of a Republika news article. The findings indicate that Republika frames the belief in Safarwadi Cave as a socio-religious problem related to collective irrationality, attributing its persistence mainly to social conformity. The media emphasizes the value of rationality as an ideal standard, as well as critical awareness of unverified claims. This framing reveals an underlying tension between local religious traditions and modern scientific perspectives within Islamic media discourse, highlighting the influential role of the media in shaping public perceptions of spiritual myths.